Legal Analysis of the Provision of Rehabilitation to Narcotics Abuse in Tanjung Pura Class IIB Detention Center - Krisley Jerani Sembiring; Yasmirah Mandasari Saragih (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The Tanjung Pura Class IIB Detention Center is one of the UPTs under the Ministry of Law and Human Rights which carries out Medical Rehabilitation and Social Rehabilitation. Rehabilitation is an effort to restore and restore narcotics abuse/addiction to health in the sense of physical, psychological, social and spiritual/religious (faith) health. With this healthy condition, it is hoped that they will be able to function normally again in their daily lives. The aim of this research is to find out the legal basis for providing rehabilitation sanctions in legislation, implementing rehabilitation. In accordance with statutory regulations and the effectiveness of rehabilitation implementation at the class IIB Tanjung Pura detention center. This research is included in analytical descriptive research with a type of empirical juridical research using qualitative analysis methods. Based on the research results, it is known that the legal basis and regulations related to rehabilitation of convicts and drug abusers are Law Number 35 of 2009 concerning Narcotics, Law Number 12 of 1995 concerning Corrections, Regulation of the Minister of Health of the Republic of Indonesia Number 46 of 2012 concerning Procedures for Implementing Rehabilitation Medical for addicts, abusers and victims of narcotics abuse. SEMA Number 4 of 2010, concerning the placement of drug abusers, victims of abuse, and narcotics addicts into medical and social rehabilitation institutions and SEMA Number 3 of 2011 concerning the placement of victims of narcotics abuse in medical and social rehabilitation institutions, implementation of rehabilitation in class IIB prisons in Tanjung Pura refers to statutory regulations related to the rehabilitation of perpetrators of criminal acts of narcotics abuse, including medical rehabilitation and social rehabilitation, until the inmates have completed their criminal term. Implementation. Rehabilitation at the Tanjung Pura class IIB detention center is quite effective in healing, educating and sensitizing prisoners, where prisoners are cured of addiction with medical rehabilitation and their personality and psychology are restored with social rehabilitation. So that after completing their prison term, inmates can return to living a normal life in society.